Coupling effects of the different temperature patterns and storage pressures on the buckling of a steel silo. (February 2022) - Ma, Yue; Bai, Rui; Yang, Li-Ping; Yang, Hong-Xia; Guo, Sheng-Dong
Abstract: Steel silos are usually located outdoors and exposed to extreme temperature variations, affecting the silo' pre-buckling deformation and buckling resistance significantly. The effects should be explicitly considered in the structural design to avoid any potential failures. Therefore, the paper investigates steel silos' buckling behaviors and derive useful design information accounting the thermal effects. Five temperature distributions are introduced to the silo walls to model the temperature variations, and two schematics of storage pressure according to the corresponding design codes are employed for comparison. The buckling behaviors of the silos are explored by employing five buckling analysis methods recommended by EN1993-1-6. The imperfections, boundary condition, and geometric parameters, i.e., aspect ratio, radius to thickness ratio, type of wall thickness, are also briefly explored. Finally, from the results of the finite element analysis, the buckling behavior of the silos under temperature variations was discussed, and conclusions were drawn.